2016
DOI: 10.3389/fpubh.2016.00169
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Hearing Health Care Disparities among Older Adults in a US-Mexico Border Community

Abstract: Hearing loss is associated with cognitive decline and impairment in daily living activities. Access to hearing health care has broad implications for healthy aging of the U.S. population. This qualitative study investigated factors related to the socio-ecological domains of hearing health in a U.S.–Mexico border community experiencing disparities in access to care. A multidisciplinary research team partnered with community health workers (CHWs) from a Federally Qualified Health Center (FQHC) in designing the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…In terms of scale, the project as a pilot study was an intentionally small, yet imperative, step toward building trust and capacity for a health education program in a topic area (hearing) that was viewed as highly new to the health center. 23 Based on the outcomes of this research, we propose that an important aspect of future program development and training within community-based interventional audiology should be a process to define the community-clinical linkages between public health and audiology. Such a process would involve identifying local resources (both community based and within health care institutions), defining roles, and establishing collaborations between CHWs/ promotoras and appropriate health care providers for referral, such as audiologists, primary care physicians, as well as other specialists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of scale, the project as a pilot study was an intentionally small, yet imperative, step toward building trust and capacity for a health education program in a topic area (hearing) that was viewed as highly new to the health center. 23 Based on the outcomes of this research, we propose that an important aspect of future program development and training within community-based interventional audiology should be a process to define the community-clinical linkages between public health and audiology. Such a process would involve identifying local resources (both community based and within health care institutions), defining roles, and establishing collaborations between CHWs/ promotoras and appropriate health care providers for referral, such as audiologists, primary care physicians, as well as other specialists.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was an evolution of an academic-community collaboration between audiology, public health, and a rural federally qualified health center (FQHC) to increase community engagement on hearing and to develop a culturally relevant hearing health education outreach program for Hispanic/ Latino older adults. 23 The CHWs involved in health promotion activities at the FQHC received specialized training about hearing loss and communicating effectively with individuals and families with hearing loss. 24 In the current research, CHWs served as cultural brokers and community health educators.…”
Section: Abstract: Interventional Audiology Community Health Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified rural/urban differences in workforce distribution across the country in primary care and otolaryngology (Vickery & Cabrera-Muffly, 2016). In addition, a community needs assessment in a rural part of Arizona identified that there is a high need for hearing health care services locally (Ingram et al, 2016). Therefore, we hypothesized that members of the hearing aid dispensing workforce would be concentrated to more densely populated areas of the state.…”
Section: Estimationsmentioning
confidence: 97%
“…The Oyendo Bien pilot study leveraged a longstanding relationship between an academic institution and a rural FQHC to conduct systematically a community needs assessment and build a basis for steering subsequent work. 57 Findings from qualitative assessments informed the iterative development of the pilot program by adapting them into core intervention components. 26 Applications of CBPR helps translate research findings into social change by integrating community participation from the beginning.…”
Section: Community-based Participatory Research As a Framework To Addmentioning
confidence: 99%